PERPECAHAN DAN SOLIDITAS ELITE PARTAI GOLKAR PADA PEMENANGAN PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA TERNATE TAHUN 2015 - Sofyan Muhamad (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Buton, 2021)
Conflict and Division of political parties in Indonesia is not a new issue. Still, the phenomenon had long been party Schism happened before, in the era of reform party politics have always been in a split case with hit never finished, one of the political parties are Golongan Karya, the ruling party during the new order Government has always been conflicts and the party's internal divisions, the year 2014 Golongan Karya again struck with the dynamics of the Division and gave birth to the dualism of the DPP at the level of stewardship, this research aims to look at the Division and solid elite DPD I Golongan Karya North Maluku on winning the election for mayor of the ternate year 2015. this research method used was qualitative case study method, in the technique of collecting data using interviews, documentation, and the withdrawal of conclusion; in this study, the theory used to analyze problems is an approach institutional political party, with this theory, the author can see solid and elite divisions Golongan Karya ternate city in the regional head election momentum the year 2015. The results of the research some problems that occurred in the inner Golongan Karya ternate city, that the occurrence of structural conflict between Leader DPD I North Maluku with DPD II city of Ternate, in addition, there is also a policy dismissal several party cadres of the ternate town conducted by Chairman of DPD I North Maluku, the split of the party in the region are inseparable with the dynamics of the political elite at the central level, that the break at the level of DPP implicates against a decline of votes in the election of Golongan Karya regional heads of ternate city, the party defeats 2015 work on the caused level of the solid elite is not well-formed, and this dismissal policy is the starting point of the party elite and splits in the political interest of the element value in the selection of the head of the regional city of Ternate.